Road maintenance planning using network flow modelling - Yang, Chao; Remenyte-Prescott, Rasa; Andrews, John (Oxford University Press, 2015)
This paper presents a road maintenance planning model that can be used to balance out maintenance cost and road user cost, since performing road maintenance at night can be convenient for road users but costly for highway agency. Based on the platform of the network traffic flow modelling, the traffic through the worksite and its adjacent road links is evaluated. Thus, maintenance arrangements at a worksite can be optimized considering the overall network performance. In addition, genetic algorithms are used for maintenance planning in order to find the best maintenance arrangements for the worksites. The key variables in the optimization model involve the starting time of maintenance works during the day, their duration, the duration of the break during the maintenance work and traffic signal controls at the worksite.